Climate, Science and Society: A Primer - Zeke Baker; Tamar Law; Mark Vardy; Stephen Zehr (Routledge, 2024)
Climate, Science and Society: A Primer makes cutting-edge research on climate change accessible to student readers. The primer consists of 37 short chapters organized within 11 parts written by Science and Technology Studies (STS) and other social science scholars. It covers a range of key topics including communication, justice and inequality, climate policy, and energy transitions, situating each one within the context of STS studies. Each reading translates a focused area of climate change research into short, accessible, and lively prose. Chapter authors open debates where relevant, consider policy implications, critique existing areas of research, and otherwise situate their reading within a larger body of research relevant to climate change courses. Designed as a jumping-off point for further exploration, this innovative book will be essential reading for students studying climate change, STS, environmental sociology, and environmental sciences.
Keywords: 550; Climate change; Climate engineering; Environmental governance; environmental inequality; environmental justice; Sociotechnical transitions; Sustainability; science; technology and society